2010
DOI: 10.1590/s0004-27302010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of scintigraphy and ultrasonography to the prediction of malignancy in thyroid nodules with indeterminate cytology

Abstract: Objective: To evaluate the contribution of 131 I scintigraphy and ultrasonography to the prediction of malignancy in thyroid nodules with indeterminate cytology in euthyroid patients. Subjects and methods: The sample consisted of 102 patients with thyroid nodules, submitted to FNAC and presenting an indeterminate cytological diagnosis (follicular neoplasm). Results: Malignancy was observed in 19/25 (76%) nodules with suspicious ultrasonographic characteristics versus 5/77 (6.5%) without suspicious findings. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
2
17
0
3
Order By: Relevance
“…However, when it was analyzed, only the 378 (15% of 2,468) patients were surgically treated in that studied group; the distribution of diagnoses was 10% of unsatisfactory sample and 61.4% of follicular lesion [13], similar to our data featuring 56% of indeterminate results. According to the literature, the frequency of malignancy in thyroid nodules <3-4 cm with indeterminate cytology (follicular neoplasms) ranges from 10% to 30% [8,26,27], which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, when it was analyzed, only the 378 (15% of 2,468) patients were surgically treated in that studied group; the distribution of diagnoses was 10% of unsatisfactory sample and 61.4% of follicular lesion [13], similar to our data featuring 56% of indeterminate results. According to the literature, the frequency of malignancy in thyroid nodules <3-4 cm with indeterminate cytology (follicular neoplasms) ranges from 10% to 30% [8,26,27], which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Rosário et al [8] confirmed malignancy in 23.5% of patients with indeterminate cytology, and 19 of these 25 (76%) nodules had suspicious sonographic features (P<0.05), similar to our results. This group verified the impact of cold nodule detection by I131 scintigraphic to predict malignancy (P< 0.05) [8], but these data are not found in our results. Stojadinovic et al [31] studied 216 patients with thyroid nodules undergoing US, electrical impedance scanning, and FNAC prior to thyroidectomy [31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The iodine radioisotopes are absorbed and organified by the thyroid and are the preferred isotypes because 3 to 8% of nodules that are hyperfunctioning when mapped with 99m Tc scans are hypofunctioning with iodine (36). Scintigraphy is also indicated for nodules with cytology, which is suggestive of follicular tumor in patients with normal low or low TSH, if it was not performed earlier (37).…”
Section: Isotope Scintigraphymentioning
confidence: 99%